Mali : Transport Support to Sustainable Economic Growth - World Bank (Washington, DC, 2013)
This Economic and Sector Work (ESW) is consistent with the objectives laid out for the transport sector in the Poverty Reduction Strategy Paper (PRSP), and the Country Assistance Strategy (CAS), with its two primary objectives focused on strengthening existing reforms, and, helping define a forthcoming reform program. The proposed transport sector strategy relies on three pillars to: 1) promote sustainable development of transport infrastructure, ensuring adequate allocation of financial, and human resources to infrastructure maintenance; 2) increase transport sector efficiency, through sound market, and fiscal policies that support the rapid modernization of Mali's transport companies; and, 3) support cross sectoral initiatives, primarily in the areas of economic competitiveness, road safety, rural poverty alleviation, and in addition, to support HIV/AIDS prevention, and health services accessibility. Since transport costs represent a significant share of the imported costs of intermediary goods used in building up Mali's export capacity, their reduction should have a positive impact on Mali's economic competitiveness. Accordingly, the already completed privatization of the railway, the current attempt at privatizing the airport system, as well as the proposed measures to increase the productivity of Mali's truck transport, should all support economic competitiveness. The Government however, should foresee that adequate regulatory oversight is in place, to ensure that these productivity gains are passed on to transport customers. Regarding road safety in Mali, it is not only a financial dimension, but also a health dimension, since it tends to challenge an already stretched health service. This would entail training law enforcement agents, towards creating a nationwide road accident database. It is stressed that the development of a rural road maintenance, and construction strategy by no later than the end of 2004, be conducted, with part of this strategy's investment priorities defined, based on poverty reduction criteria, such as increased accessibility to health care, linkage to local markets, and other potential accessible services. The report emphasizes it is now an established fact, that transport activities are an important vector to HIV/AIDS dissemination, where activities within the transport sector, designed to educate transport operators about the disease, and its mode of transmission would, contribute to the overall fight against the spread of the epidemic.